2011
DOI: 10.1038/icb.2011.22
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and mechanisms of action of vitamin D in experimental polyarthritis

Abstract: Vitamin D (vit D) status has been linked to the occurrence and severity of auto-immune and inflammatory diseases. This study evaluates the effects of vit D status on adoptive transfer of adjuvant-induced arthritis (ATA). Rats maintained on diets replete or deficient in vit D3 received arthritogenic thoracic duct cells and were monitored for severity of arthritis. CD45 + cells obtained by collagenase digestion of hind-paw synovium-rich tissues (SRTs) were analysed to observe the effects of dietary vit D3 on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…Vitamin D deficiency correlates with increased disease severity and joint damage in RA (9,10) and in rodent models of arthritis (11). Treatment with vitamin D and analog VDR agonists have been shown to reduce disease severity and joint damage in experimental arthritis (12,32), including collageninduced arthritis (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency correlates with increased disease severity and joint damage in RA (9,10) and in rodent models of arthritis (11). Treatment with vitamin D and analog VDR agonists have been shown to reduce disease severity and joint damage in experimental arthritis (12,32), including collageninduced arthritis (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the role of UVR-induced vitamin D in modulating immune-driven diseases has not (until the current study) been examined in vitamin D-deficient mice. Through dietary restriction, vitamin D deficiency enhanced the pathogenesis of immune-driven disorders such as diabetes [14], colitis [15] and arthritis [16] in rodent models. However, Becklund et al (2010), observed that UVR suppressed experimental autoimmune encephalomyelitis (EAE) in mice (a murine model of multiple sclerosis) when there were minimal changes in serum 25(OH)D 3 , suggesting that vitamin D 3 may not be a central mediator of UVR-induced systemic immunosuppression [17].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have suggested that vitamin D deficiency increases the susceptibility and severity of rheumatoid arthritis (Kroger et al, 1993, Cantorna et al, 1998, Larsson et al, 1998, Cutolo et al, 2006, Patel et al, 2007, Haque and Bartlett, 2010, Rossini et al, 2010, Kerr et al, 2011, Turhanoglu et al, 2011, Zwerina et al, 2011, Attar, 2012, Moghaddami et al, 2012, Moghimi et al, 2012, Song et al, 2012). At least in the short time frame of our study, vitamin D deficiency did not appear to cause overt rheumatoid arthritis; however we can make some significant comparisons.…”
Section: 0 Discussionmentioning
confidence: 99%
“…A positive association has been observed between vitamin D deficiency and undifferentiated inflammatory arthritis (Heidari et al, 2012), a condition which frequently progresses to active RA, which suggests that vitamin D deficiency may play a role in initiation or early stage of the disease. In rodents, vitamin D deficiency or vitamin D receptor deletion increased disease severity and delayed resolution of inflammatory arthritis (Zwerina et al, 2011, Moghaddami et al, 2012). Conversely, supplementation with the active hormone, 1,25-dihydroxyvitamin D3 or a vitamin D analog prevented development or halted progression of collagen-induced arthritis, and reduced the severity of Lyme-induced arthritis (Cantorna et al, 1998, Larsson et al, 1998).…”
mentioning
confidence: 99%